Household willingness to pay for organic products - Rachel Griffith; Lars Nesheim (Centre for Microdata Methods and Practice (cemmap), 2008)
We use hedonic prices and purchase quantities to consider what can be learned about household willingness to pay for baskets of organic products and how this varies across households. We use rich scanner data on food purchases by a large number of households to compute household specific lower and upper bounds on willingness to pay for various baskets of organic products. These bounds provide information about willingness to pay for organic without imposing restrictive assumptions on preferences. We show that the reasons households are willing to pay vary, with quality being the most important, health concerns coming second, and environmental concerns lagging far behind. We also show how these methods can be used for example by stores to provide robust upper bounds on the revenue implication of introducing a new line of organic products.
Keywords: D12; L11; L81; Q51; C81; 330; Haushaltsökonomik; Willingness to pay; Biokost; Hedonischer Preisindex; Großbritannien